Erasing boundaries: Researching the emancipation process of Roma women within the framework of the heroines project - Bogdanović Bojana; Stevanović Lada; Đorđević Ivan (Glasnik Etnografskog Instituta SANU, 2025)
Contemporary societies, both globally and locally, are becoming increasingly aware of the need for inclusiveness and equality, especially when it comes to those social groups that have historically been neglected or marginalized. Women’s empowerment, in a broader context, is becoming one of the key mechanisms in the fight against discrimination and inequality. Its role is particularly significant in cases where women, in addition to gender-based, also face other forms of structural inequality - ethnic, social and economic. This is precisely the situation that characterizes the life contexts of Roma women, whose emancipation, despite the existing history of research, remains insufficiently known, especially in the context of creating deeper and more comprehensive insights into their struggles and achievements. This paper seeks to provide a new perspective on the process of emancipation of Roma women, mapping the paths of the empowerment through the analysis of the obstacles they face, but also the practices of resistance, solidarity and independent actions that build spaces of freedom and subjectivity. The authors do this based on the research conducted within the framework of the HEROINES project, supported by the Centre for the Promotion of Science, and implemented by the Institute of Ethnography of the Serbian Academy of Sciences and Arts in cooperation with the Faculty of Philosophy of the University of Belgrade and the Roma Women’s Centre “Bibija”. By applying the participatory methodology of community mapping - relatively new in Serbian social sciences and humanities - Roma women gain an active role in shaping their own stories, thereby destabilizing the traditional, paternalistic epistemological position of researchers.